Multi-Actor Sinergy in Clean Water Resource Manajement : A Study Case of Tumpeng Village, Lumajang Regency - Mokhammad Hariyadi Eko Romadon; Nizma Yuraida; Prasojo Nur Ashar Darmawan; Muhammad Mughni Labib; Muhammad Muqoffa (Trescode Green Organization, 2025)
The availability of clean water remains a fundamental necessity and a persistent challenge in various rural areas, including Tumpeng Village, Lumajang Regency. This community service project aims to describe the synergy between the community, local government, and the Public Administration Study Program of Universitas Lumajang in community-based water resource management. This program is a collaborative initiative involving Offroader Bersatu Nusantara (OBN), Quran Best Foundation, the Lumajang Regency Government, and Universitas Lumajang, focusing on the construction of artesian wells and social assistance. The methods employed include cross-actor coordination, field surveys and observations, community socialization and education, self-help assistance, participatory approaches, as well as monitoring and evaluation. The results indicate that the constructed artesian wells provide a sufficient discharge of clean water to meet local needs. Beyond the physical impact of improved water access, this initiative has increased public awareness regarding the importance of collective and sustainable water resource management. This multi-actor synergy contributes to strengthening community participation, fostering the spirit of mutual cooperation (gotong royong), and establishing local independence in clean water management. This project is expected to serve as a sustainable model for community service collaboration based on local needs.